Challenges and Responses of Artificial Intelligence Governance to Existing Laws: A Case Study of "Soft Law Path" and "Hard Law Path" - Liu, Xinyao (International Journal of Social Sciences and Public Administration, 2025)
With the wave of the third Industrial Revolution, artificial intelligence has posed a certain challenge to the existing legal system. Such challenges are mainly reflected in the conflict of law values in the process of operation and the fragmentation of artificial intelligence legislation. Based on the existing literature, this thesis compares the legislation and judicial practice of artificial intelligence in China and France, and puts forward the soft law path and hard law path to solve the above problems.